Laboratory Investigation of the Unsaturated Shear Strength Characteristics of Sand–Clay Mixtures - Gaoliang Tao; Nong Mao; ShaoPing Huang; Qing Ouyang (Advances in Civil Engineering)
Sandy-clay mixtures are commonly used in civil engineering projects, such as transportation and water resources, due to their unique construction properties. While the macromechanical characteristics of these mixtures under saturated conditions are well understood, their behavior in unsaturated states is still not fully elucidated. This study aims to investigate the mechanical behavior of sand–clay mixtures under unsaturated conditions by examining the influence of varying sand content and matric suction on their shear strength. The research includes unsaturated shear strength tests and nuclear magnetic resonance (NMR) experiments to analyze the pore characteristics within the mixtures at different sand content levels. The correlation between changes in pore structure and shear strength is systematically analyzed. The unsaturated shear strength of the mixtures is predicted using the Fredlund shear strength formula and compared with the measured values. The results indicate that the unsaturated shear strength of the mixture decreases as the sand content increases but stabilizes once the sand content reaches 20%. Below 20% sand content, the changes in micropore distribution are not significant with increasing sand content. However, beyond 20% sand content, there is a noticeable increase in the ratio of large pores and a decrease in the proportion of small pores. The sand content of 20% represents a critical threshold for the strength and porosity variations in the mixture. Under constant matric suction, the unsaturated shear strength of the mixture improves with the increase in sand content. However, the predictive accuracy of the Fredlund shear strength formula gradually diminishes as the sand content increases.